Adherence to Iron- Folic- Acid Supplementation and its Related Factors among Pregnant Women in Mazandaraz, Iran in 2022 - Pegah Salehi; Mojgan Firouzbakht (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2023)
Introduction: Adhering to the daily intake of folic acid-iron during pregnancy reduces maternal complications such as premature birth, low birth weight and fetal defects. It seems necessary to identify factors related to iron/ folic acid adherence. This study was conducted with aim to determine the adherence to iron- folic acid supplementation and its related factors among pregnant women.Methods: This descriptive-analytical study was conducted in 2022 on 178 pregnant women in Mazandaran province/ Iran. Data were collected via questionnaires (Demographic, self-report adherence, Morisky questionnaire and Iron/ folic acid knowledge). Analysis was done using SPSS software (version 21) and chi-square test and logistic regression analysis. P<0.05 was considered statistically significant.Results: Nearly 70% of pregnant women adhered to iron-folic acid intake. The most observed side effects were gastrointestinal complications, and the most common reason for non-adherence to use was forgetfulness. Age over 30 years old (OR=2.49; p=0.027), prenatal care more than 4 times (OR=2.33; p=0.042), and the absence of drug side effects (OR=2.42; p=0.033) increased the chances of adhering to iron-folic acid. The chance of adhering decreased in working mothers (OR=0.33; p=0.025).Conclusion: In this study, adherence to iron and folic acid intake in pregnant women was high. Regular prenatal care and appropriate consultation will improve adherence to iron/folic acid intake in pregnant women.